An Analysis of Factors of Student’s Difficulties in Listening Comprehension - Fadli, Moch; Kurniasari, Renny; Amalia, Hariana (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
Listening comprehension in the learning process greatly helps increase students’ performance in mastering English listening skills students and to understand the topic or lesson being studied. The purpose of this research to find out students’ difficulties in listening comprehension. Based on what the researcher observed when doing preliminary with some students, it seems they have difficulties when doing an exercise in listening comprehension. In this research mixed method were used. The researcher took 34 participants of the students and for the interview sections, the researcher took 6 students from 34 students in the class of XI IPA 1 at the year eleventh of SMA Tunas Bangsa. The data were gathered by using questionnaire and interview adapted by Hamouda (2013) in the classroom. Based on the research findings, the researcher found out that the most of students at the year eleventh of Senior High School Tunas Bangsa have various difficulties in listening comprehension such as (1) unfamiliar words in listening material, (2) unfamiliar topics of linguistics, (3) unable to concentrate, (4) students’ anxiety, (5) the audiences’ factors, (6) the audio factors, and (7) physical environmental.